2006
DOI: 10.1002/anie.200503222
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Nitrogen–Hydrogen Bonds of Ammonia Induced by Triruthenium Polyhydrido Clusters

Abstract: NÀH bond activation of amines has attracted increasing attention owing to its applicability to the synthesis of various amino compounds, and the development of a new and effective reaction system for the activation of ammonia must be one of the most important research targets in connection with the transformation of abundant and inexpensive ammonia into a useful amino compound.[1] However, successful examples of activation of the NÀH bond of ammonia are still rare because of both the high NÀH bond dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
63
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 30 publications
(18 reference statements)
0
63
0
Order By: Relevance
“…4 Complex 1 fully realized the cooperative action of metal centers in the bondbreaking step of compounds such as saturated and unsaturated hydrocarbons, nitriles, 5 and ammonia. 6 It was also demonstrated that complex 1 is a suitable soluble model of adsorption sites for benzene 7 and pyridine 8 on a close-packed metal surface. …”
Section: Introductionmentioning
confidence: 99%
“…4 Complex 1 fully realized the cooperative action of metal centers in the bondbreaking step of compounds such as saturated and unsaturated hydrocarbons, nitriles, 5 and ammonia. 6 It was also demonstrated that complex 1 is a suitable soluble model of adsorption sites for benzene 7 and pyridine 8 on a close-packed metal surface. …”
Section: Introductionmentioning
confidence: 99%
“…[8] New routes resulting in the activation of NÀHb onds in ammonia are particularly appealing because of the dearth of transition-metal systems capable of effecting such atransformation [9][10][11][12][13][14][15][16][17][18][19][20][21] and the relevance of N À H activation to an umber of potentially important industrial processes. [22] In addition to these high profile examples,r ecent studies have shown that complexes of phosphorus(III) with distorted geometry can cleave arange of polarized EÀHbonds (E=Oor N).…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Therefore,a dvances in main group mediated activation of ammonia are of great interest. [4, 5, 6c-d,24, 26, 27, 30-32] Ther eaction of 1 with ammonia gas (1 atm) results in the quantitative conversion of 1 to anew product, 2 (Scheme 2).…”
mentioning
confidence: 99%
“…Noteworthy, to the best of our knowledge, this is the first example of a low-valent late metal mixed parent imido/amido complex ever reported. (14), Ir1-Ir2 2.7758(2), Ir1-Ir1' 2.8572(3), Ir1-H 1.788 (19); Ir1'-Ir1-Ir2 59.025(4), Ir1-Ir2-Ir1' 61.950 (8), N1-Ir1-N1' 73.58 (16), N1-Ir2-N1´ 73.79 (19), Ir1-N1-Ir2 86.90(13), Ir1-N1-Ir1' 89.90 (13). Ct represents the midpoints of the olefinic bonds.…”
mentioning
confidence: 99%
“…[19] In this context, the transformation of a methoxo diiridium compound to imido clusters 2 and 3 upon interaction with ammonia can be viewed formally as a multiple activation of ammonia. The mere existence of parent imido complexes of late metals (Co triad and after) in low oxidation states is extremely rare, situation explained in terms of d p repulsions between the metal and the nucleophilic nitrogen centres.…”
mentioning
confidence: 99%